2004
DOI: 10.1590/s0004-282x2004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic features of Guillain-Barré syndrome in São Paulo, Brazil

Abstract: INTRODUCTION: There are few epidemiologic studies concerning Guillain-Barré syndrome (GBS). Due to difficulties with definition and lack of a standard diagnostic test of reference, GBS is not easy to study epidemiologically. We evaluate some epidemiological features of GBS in a sample of cases treated at a tertiary hospital in São Paulo, Brazil. METHOD: We retrospectively reviewed all cases of GBS with hospitalization in Santa Marcelina hospital, over the period of January 1995 through December 2002. RESULTS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 24 publications
2
41
2
5
Order By: Relevance
“…reported a higher percentage in males which is in accordance with our study 2,3,4 . However, a study by Farhoudi et al reported a higher percentage in females 5 .…”
Section: Studies By Rees Et Al Yuan Et Al and Rocha Et Alsupporting
confidence: 93%
“…reported a higher percentage in males which is in accordance with our study 2,3,4 . However, a study by Farhoudi et al reported a higher percentage in females 5 .…”
Section: Studies By Rees Et Al Yuan Et Al and Rocha Et Alsupporting
confidence: 93%
“…For other parts of the world, very few studies were found, and therefore it is difficult to comment on any geographical trends. For the data presented, a comparison of these rates with those of Europe and North America suggest that incidence was lower in China [12,13] , Hong Kong [14] and Brazil [15] , similar in Tanzania [21] , Australia [16,17] and Japan [18] and slightly higher in the Middle East [19,20] and Curaçao [9] .…”
Section: Geographical Variationmentioning
confidence: 86%
“…1,[4][5][6]16,[19][20][21] Some of these studies show more cases in colder months. 16,21 One of the largest epidemiological studies conducted in southwest Netherlands 4 shows more cases during the winter and June, in Brazil a cluster of cases in spring and summer was reported 22 and in Sweden autumn was the season with most GBS cases. 23 The seasonality prompted us to search for specific infectious triggers.…”
Section: Discussionmentioning
confidence: 99%